Social Determinants of Health of Child Marriage (Analysis of IFLS 2000, 2007, 2014) (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2019)
Early marriage is defined as a marriage of women aged 18 years old. The current world prevalence is declining, but when compared with the growth in population, the total number of married children tends to increase. Today, early marriage reaches 41.000 every day, especially in Sub-Saharan Africa and South Asia. This research aims to identify the social determinants of health that encourage early marriage. This research used a quantitative observational analytic study with cross-sectional design. The number of 18 year-old married women were 1.96% (IFLS5), 18 year-old married men were 0.15% (IFLS5). The average age at first birth was 22.96 years old. The economic status of early marriage was mostly in Quintile 1, and the majority of residences were in rural area. The ratio of married women and men aged 18 years old was 11-14: 1. Employment, education, residence and poverty were associated with early marriage and were statistically significant.